Marine Macrophyte - An Alternative Livelihood for Coastal Community - Doss, Asirvatham; Radhika, Duraisamy; Rajalakshmi, Ramakrishnan (Asian Journal of Biological and Life Sciences)
Background: Coastal fisher folk, especially fisher women find mass propagation of seaweed is an economically smart alternative livelihood. In Tamil Nadu, in the year 2000, the fishing villages of Ramanathapuram District Gulf of Mannar, South-East coast of India, started seaweed farming on industrial scale. Knowing the economic feasibility of seaweed farming, the fishermen were encouraged to farm seaweed on a large scale. In this paper, an assessment was carried out on the socioeconomic status of fisher folk who farm seaweed in the Tuticorin District, Tamil Nadu is presented. The economically viable Kappaphycus alvarezii, a red alga, is extensively cultivated along the coastal waters of Tamil Nadu. Materials and Methods: Experiments were conducted in the shallow subtidal waters on the southeast coast of India at Kovalm Beach, Thoothukudi. From January to the present (2022), the monocline synthetic rope (16 mm in diameter) culture of K. alvarezii was tested. Results and Conclusion: In the present study, it is found that the total cost of production for construcing a single monoline plot [94 long-line ropes (94x18)] was 35, 000/-. The harvest cycle from planting to harvesting took 33 days with a yield of 80 kg per long-line rope. Based on the current selling price of Rs. 6 per kg of fresh Kappaphycus alvarezii from the long-line rope farming method adopted, a seaweed farmer earned Rs. 45, 120/- per plot.
Keywords: Constraints; Economic status; Kappaphycus alvarezii; Monoline method; Seaweed